Наукова школа доктора біологічних наук професора Л.І. Рубцова - Rubtsova, O.L.; Chuvikina, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to explore the scientific school of the famous landscape architect, dendrologist, doctor of biological sciences professor Leonid Ivanovich Rubtsov. Material and methods. Creative biographies of L.I. Rubtsov’s post graduate students have been analyzed. The historical- scientific method and method of interviews were used. Results. The theoretical scientific developments of L.I. Rubtsov, set out in unique monographs, and his ideas are implemented practically during the construction a number of botanical gardens and parks were investigated. Professor Rubtsov worked fruitfully for 50 years in the field of dendrology and green building. In M.M. Gryshko National Botanical Garden of the NAS of Ukraine Leonid Ivanovich was the author and the head of the work on the arboretum creation. In 1972 the Botanical Garden was granted the status of a monument of landscape art of national importance. This became possible thanks to works of L.I. Rubtsov. His knowledge and great experience he passed on to his students, who eventually became good experts in dendrology and landscape architects. Professor L.I. Rubtsov was the head of 8 post graduate students (Candidates of Sciences): namely 3 Candidates of Architecture (I.D. Rodichkin, V.G. Maevskaya, V.I. Meshkova) and 5 Candidates of Biological Sciences (M.I. Orlov, Yu.K. Kirychek, M.F. Kaplunenko, B.K. Gryshko-Bogmenko, N.F. Kolybina). Conclusions. Erudition, a wide range of interests and style of work of Leonid Ivanovich were of decisive importance for attracting young talents and for many years determined their creative ways. Scientific works of L.I. Rubtsov, especially monographs, reference books and manuals are still indispensable benefits for many specialists in the field of landscape architecture and decorative gardening.